Engaging women with an embodied conversational agent to deliver mindfulness and lifestyle recommendations: A feasibility randomized control trial. Issue 9 (September 2017) - Gardiner, Paula M.; McCue, Kelly D.; Negash, Lily M.; Cheng, Teresa; White, Laura F.; Yinusa-Nyahkoon, Leanne; Jack, Brian W.; Bickmore, Timothy W.
Highlights: It is feasible to use an ECA to teach healthy behaviors among urban women. Stress management techniques can be developed through interaction with an ECA. An ECA can also be used to increase fruit consumption. More research is needed on using ECAs to replace patient information sheets. Abstract: Objective: This randomized controlled trial evaluates the feasibility of using an Embodied Conversational Agent (ECA) to teach lifestyle modifications to urban women. Methods: Women were randomized to either 1) an ECA (content included: mindfulness, stress management, physical activity, and healthy eating) or 2) patient education sheets mirroring same content plus a meditation CD/MP3 once a day for one month. General outcome measures included: number of stress management techniques used, physical activity levels, and eating patterns. Results: Sixty-one women ages 18 to 50 were enrolled. On average, 51% identified as white, 26% as black, 23% as other races; and 20% as Hispanic. The major stress management techniques reported at baseline were: exercise (69%), listening to music (70%), and social support (66%). After one month, women randomized to the ECA significantly decreased alcohol consumption to reduce stress (p = 0.03) and increased daily fruit consumption by an average of 2 servings compared to the control (p = 0.04). Conclusion: It is feasible to use an ECA to promote health behaviors on stress management and healthy eating among diverse urban women. Practice implications: Compared to patient information sheets, ECAs provide promise as a way to teach healthy lifestyle behaviors to diverse urban women.